2014
DOI: 10.3391/ai.2014.9.1.08
|View full text |Cite
|
Sign up to set email alerts
|

Distribution and current status of non-indigenous mollusc species in Lithuanian inland waters

Abstract: In the Laurentian Great Lakes, the invasive form of Phragmites australis (common reed) poses a threat to highly productive coastal wetlands and shorelines by forming impenetrable stands that outcompete native plants. Large, dominant stands can derail efforts to restore wetland ecosystems degraded by other stressors. To be proactive, landscape-level management of Phragmites requires information on the current spatial distribution of the species and a characterization of areas suitable for future colonization. U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…In Lithuania, L. naticoides was mainly found in running waters, mostly in sites at the Nemunas River and also at some of its tributaries not far upstream from their confluences. The lentic sites where this species was detected are located in the Curonian Lagoon, and Kaunas and Elektrėnai water reservoirs (Butkus et al ., 2014). In Hungary, L. naticoides is widely distributed in the Danube River and its main tributaries (Bódis et al ., 2012).…”
Section: Introductionmentioning
confidence: 99%
“…In Lithuania, L. naticoides was mainly found in running waters, mostly in sites at the Nemunas River and also at some of its tributaries not far upstream from their confluences. The lentic sites where this species was detected are located in the Curonian Lagoon, and Kaunas and Elektrėnai water reservoirs (Butkus et al ., 2014). In Hungary, L. naticoides is widely distributed in the Danube River and its main tributaries (Bódis et al ., 2012).…”
Section: Introductionmentioning
confidence: 99%
“…It is expected that the species range will increase exponentially across the five continents. In European waters the species has been present for more than 100 years, and its further expansion in temperate freshwater ecosystems is still ongoing (Rakauskas et al, 2007;Butkus et al, 2014), which is already noted in the neighbouring invaded areas. Alonso et al (2019) have shown that the species has invaded the entire Iberian Peninsula and it is in a clear spreading phase, which makes its control very difficult, especially because of its non-water mediated dispersion mechanisms (e.g., mud or birds).…”
Section: Introductionmentioning
confidence: 92%
“…However, stress exposure may also lead to the disappearance of P. acuta as in Lithuanian inland waters (Europe) where the locally established snail was not recorded since 1950s, possibly due to long term application of herbicides and consequent depletion of oxygen and/or food resources (Buktus et al 2014).…”
Section: ) Larval Trematodes Acting As Biotic Stressors And/or Stresmentioning
confidence: 99%